ANALISIS PENGARUH TINGKAT INVESTASI DAN TENAGA KERJA TERHADAP PDRB PROVINSI LAMPUNG PERIODE 2012-2021 - Julian, Nabila Arnelis; Melati, Puput; Utami, Endang Mega; Rahmaillah, Windy; Purwaningsih, Vitriyani Tri; Aida, Neli (ANALISIS, 2023)
GDRP is a measure of a region's economic progress. Changes in the level of GDRP can be used to measure the level of economic development of each region. Two factors that can affect GDP are labor and investment levels. This research was conducted to determine how the impact of employment and investment on GRDP in Lampung Province from 2012 to 2021. Utilize data processing tools or STATA version 14 programs. This study used multiple linear regression models, conventional assumption tests, t and f tests to verify the validity of hypotheses. This approach involves quantitative research with secondary data. Cross sectional data was the form of data used in the study. The data used in this study came from the Badan Pusat Statistik (BPS). According to research findings, investment in Lampung Province from 2012 to 2021 had a positive but not significant influence on GDRP. In Lampung Province in the same year, labor had a positive and significant influence on GDRP.